2021
DOI: 10.1590/s1678-3921.pab2021.v56.02468
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and stability with multivariate definition of macroenvironments for wheat yield in Rio Grande do Sul

Abstract: The objective of this work was to evaluate the adaptability, stability, and environmental stratification of wheat (Triticum aestivum) grown in 20 environments, in the state of Rio Grande do Sul, Brazil. The experiments were performed during four crop years, in five wheat growing regions, considering 20 distinct growing environments. In the presence of genotype x environment (GxE) interaction, the additive main effects and multiplicative interaction analysis (AMMI) method was used. This method combines variance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This interaction refers to how different genotypes respond variably to different environmental conditions (Cruz, Carneiro, & Regazzi, 2014;. Through multi-environment tests, it is possible to identify and select groups of environments with similar conditions, called mega-environments (Katsenios et al, 2021;Szareski et al, 2021). Therefore, one can identify genotypes that can be cultivated within these mega-environments.…”
Section: Positioning Genotypes In Mega-environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction refers to how different genotypes respond variably to different environmental conditions (Cruz, Carneiro, & Regazzi, 2014;. Through multi-environment tests, it is possible to identify and select groups of environments with similar conditions, called mega-environments (Katsenios et al, 2021;Szareski et al, 2021). Therefore, one can identify genotypes that can be cultivated within these mega-environments.…”
Section: Positioning Genotypes In Mega-environmentsmentioning
confidence: 99%
“…Simultaneously with the development of genotypes tolerant to abiotic stress, the identification of environments with similar environmental conditions, known as megaenvironment assessment, improves the efficiency of genotype positioning (Katsenios et al, 2021). Studies have identified the presence of mega-environments in several cultures, as highlighted by Katsenios et al (2021), Szareski et al (2021) and Savicki et al (2023). This approach allows positioning genotypes within these mega-environments, which results in reduced costs in genetic breeding programs (Nardino et al, 2018) and provides favorable phenotypic responses.…”
Section: Introductionmentioning
confidence: 99%